Homework for New Changes in The Future: A Bibliometric Analysis - Andika Wulan Febriani; Madziatul Churiyah (Journal of Business and Management Review, 2022)
This literature review focuses on the relationship between working from home (WFH) and the new future order. The method employed is a bibliometric literature review that was examined using VOSviewer software. The VOSviewer software analysis technique was used to assess papers produced via the Scopus database and utilized as a reference for researchers. The findings of 315 papers were cited from 2020 to 2022, with just 40 articles being evaluated. The researchers then clarified and visualized co-authorship, co-accurance, and citation using VOSviewer softwareThis literature review, as a whole, provides a reliable starting point for additional research on the topic at hand. Working from home refers to a variety of methods of working that are common among today's workers. Working from home is a flexible and automated work method that allows employees to work from home via telecommuting, teleworking, and remote work by leveraging modern digital technology tools as a bridge to work. All men and women between the ages of 25 and 60 can work from home. Working flexibly in the "New Normal" focuses on the new order in the possibility of working from home is more focused on using SWOT analysis, which intends to read and observe working from home in the future